2019
DOI: 10.3390/nu11020395
|View full text |Cite
|
Sign up to set email alerts
|

Red Quinoa Bran Extracts Protects against Carbon Tetrachloride-Induced Liver Injury and Fibrosis in Mice via Activation of Antioxidative Enzyme Systems and Blocking TGF-β1 Pathway

Abstract: The late stages of liver fibrosis are considered to be irreversible. Red quinoa (Chenopodium formosanum Koidz), a traditional food for Taiwanese aborigines, was gradually developed as a novel supplemental food due to high dietary fibre and polyphenolic compounds. Its bran was usually regarded as the agricultural waste, but it contained a high concentration of rutin known as an antioxidant and anti-inflammatory agent. This study is to explore the effect of red quinoa bran extracts on the prevention of carbon te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Previous studies have also indicated that RQS contains anthocyanins, betacyanins, and flavonoids (quercetin and rutin) in valuable amounts. These compounds have been proven to perform antioxidative and anti-inflammatory effects in rats with hepatic damage [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have also indicated that RQS contains anthocyanins, betacyanins, and flavonoids (quercetin and rutin) in valuable amounts. These compounds have been proven to perform antioxidative and anti-inflammatory effects in rats with hepatic damage [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The administration of 30 mg kg −1 RQS was more efficient than YQS, which might be due to the high content of polyphenols and AOA in RQS. The enzymatic antioxidant defense system, such as SOD and glutathione enzymes are important scavengers of active radicals [ 57 ]. RQS and YQS attenuated GSH, SOD, and MDA levels close to the NR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Djulis (Chenopodium formosanum) is a native cereal crop planted in Taiwan and traditionally called "ruby of cereals" for its bright red color. Djulis has many health benefits, such as anti-adipogenesis [13] and recovering liver injury [14,15]. Some studies found that the color of djulis was mainly from betalains, including betanin, isobetanin, amaranthine, and isoamaranthine, which were directly related to its antioxidant capacity [16].…”
Section: Introductionmentioning
confidence: 99%